Development of core competency index system for stomatological nurse specialist (口腔专科护士核心能力框架的构建) - WU Hong (吴宏); FENG Zhien (冯芝恩) (中西医结合护理)
Objective To develop the core competency index system for stomatological nurse specialist. Methods Based on literature review, the core competency index system was developed by two rounds of Delphi method. Results The expert questionnaire enthusiasm coefficient was all 100%, and the average authority coefficient was 0. 891, variation coefficient was lower than 0. 25. The core competency index system eventually included 4 first-level indexes which were clinical practice ability, nurse consulting ability, research ability, management ability, and 22 secondary indexes. Conclusion The core competency index system for stomatological nurse specialist is scientific, reasonable and credible. It provides objective basis for comprehensive specialized development of nurses' ability. (目的 为构建国内口腔专科护士核心能力框架, 促进口腔专科护士能力的专业化发展、培训以及评价专科护士提供依据。方法 在文献回顾的基础上, 采用德尔菲法进行2轮专家咨询, 从而构建口腔专科护士核心能力框架。结果 2轮专家咨询的积极性系数均为100%, 平均权威系数为0. 891, 专家意见集中协调度0. 13, 变异系数＜0. 25, 最终确立口腔专科护士核心能力框架包括4个一级指标和22个二级指标, 其中一级指标包括临床实践能力、护理咨询能力、科研能力以及管理能力。二级指标包括正确应用护理程序, 专科理论知识, 探索新理论、新知识以及与患者沟通能力等。结论 构建了具有科学性、合理性和可信性的口腔专科护士核心能力框架, 为提升护士能力的全面发展提供了客观依据。)